Wizards of the galaxy - Morris, Gilbert; Meeks, Dan. (Chicago : Moody Press, 1998)
Six Junior Space Rangers try to find a way to defeat the wizards who rule the planet Merlina and keep them from gaining control of other planets.
Keywords: Science fiction; Christian life -- Fiction